Vom Scheitern einer Studie in Maßregelvollzugskrankenhäusern: klinische Prüfung zum additiven Effekt von Triptorelin auf die Wirksamkeit von Psychotherapie = Failure of a study in forensic psychiatric hospitals - Briken, Peer; Kasperk, Christian (Der Nervenarzt, 2017)
Background: A testosterone-lowering medication is relatively commonly used as a form of treatment for sexual offenders with severe paraphilic disorders in German forensic psychiatric hospitals; however, a double-blind, controlled and randomized study, which investigates the efficacy of this medication, is still lacking.AimThis article describes the process from the planning to the rejection of a clinical trial over the period from 2009 to 2015.Methods and resultsDespite the careful planning with an interdisciplinary team and giving special consideration to the complex legal situation, the Federal Institute for Drugs and Medical Devices (BfArM) rejected the proposed trial in a brief formal letter with reference to the German Drug Law (§ 40 para. 1 p. 3 nr. 4 AMG). The ethics committee of the Hamburg Medical Association considered that clinical research is basically not possible with patients detained in a forensic psychiatric hospital.DiscussionIn the opinion of the authors, the described facts illustrate how legal regulations that should protect vulnerable groups in medical research, in a specific case can lead to the fact that a therapy form relevant to the corresponding patient group cannot be scientifically investigated.
Gesehen am 19.07.2018